Entropy generation in radiative flow of Ree-Eyring fluid due to due rotating disks. Issue 4 (23rd September 2019) - Khan, Muhammad Ijaz; Ahmad Khan, Sohail; Hayat, Tasawar; Faisal Javed, Muhammad; Waqas, Muhammad
Abstract : Purpose: This paper aims to address the flow features of Ree–Eyring fluid between two rotating disks subject to the magnetic field. Heat transfer features are discussed through viscous dissipation and nonlinear thermal radiation. Impact of thermophoresis and Brownian movement are elaborated. Physical characteristics of entropy generation optimization in nanofluid with homogeneous and heterogeneous chemical reaction are discussed. Design/methodology/approach: The nonlinear system leads to ordinary one through the implementation of adequate transformation and then tackled analytically for a convergent series solution by homotopy analysis method. Findings: The prime objective of the present research has been given to investigate entropy generation in Ree–Eyring fluid flow between two rotating disks subjected to the magnetic field. Vital features, namely, Brownian motion and thermophoresis have been addressed. Total entropy rate is computed using the second law of thermodynamics. Originality/value: No such work yet exists in the literature.